Comparison of Microleakage of CEM Cement Apical Plug in Different Powder/ Liquid Ratio in Immature Teeth Using Fluid Filtration Technique - Fatemeh Ayatollahi; Fatemeh Zarebidoki; Seyed Hossein Razavi; Mahdi Tabrizizadeh; Reza Ayatollahi; Mahyar Heydarigujani (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Sealing ability is one of the most important factors for successful endodontic treatment. Some studies have shown that the powder to liquid ratio can influence the properties of dental materials. Subsequently, this may happen for those used for sealing in endodontics. Purpose: The purpose of this research was to assess the microleakage of calcium-enriched mixture (CEM) cement apical plug in different powder to liquid ratio. Materials and Method: Ninety-six extracted human single root and single canal teeth were decoronated. Working length was determined using ≠15 k-file. Canal preparation was performed using step back method. Samples were divided into 3 groups randomly. CEM cement was placed into the canal with 1.13, 2.27 and 3.40 powder to liquid ratio in the group 1, 2 and 3, respectively. After complete setting of CEM cement, the micro leakage value was evaluated using fluid filtration method. Data were analyzed using ANOVA and Scheffe tests. Results: The bubble movement in three groups showed a statistically significant difference (p< 0.001). Minimum and maximum bubble movements were observed in the group with powder to liquid ratios of 3.40 and 1.13 respectively. Conclusion: Increased CEM Cement powder to liquid ratio will increase the sealing ability of this material as apical plug. Considering the conditions of this study, the powder to liquid ratio of 3:40 provided the best sealing ability.